Dual interfacial modification of hematite electron transport layer for efficient and stable perovskite solar cells - Abu Summama Sadavi Bilal; Muhammad Meesum Bilal; Muhammad Faheem Zia; Shazia Feroz; Muhammad Nauman Ullah; Muhammad Ajmal Khan; Nargis Bano; Ijaz Hussain; Rida Fatima (Results in Engineering)
This research investigates the dual interfacial modification of hematite (Fe₂O₃) electron transport layers (ETL) in perovskite solar cells (PSCs) by introducing 4-trifluorophenylammonium iodide (CF₃PhAI) to improve device performance and stability. The device configuration, ITO/αFe2O3/CF3PhAI/Perovskite/CF3PhAI/Spiro-OMeTAD/Au, aims to address interfacial challenges and charge recombination, which often limit PSC efficiency. The CF3PhAI interfacial layer applied both above and below the perovskite layer, effectively passivates interfacial defects, improves charge extraction, and reduces recombination. This dual interfacial modification resulted in a significant efficiency improvement, with the target device achieving a power conversion efficiency (PCE) of 15.63 %, outperforming devices with single (14.26 %) or no interfacial layers (10.93 %). The optimized device retained 55 % of its initial efficiency after 250 h under continuous testing, a notable improvement over the other devices. Characterization techniques, including JV curves, PL, TRPL, and SCLC measurements, were utilized to analyze the improvements in charge transport, recombination, and overall device performance. This study highlights the potential of CF3PhAI as a dual interfacial layer, providing an effective approach to increase both the efficiency and stability of PSCs and contributing valuable insights into the development of commercially viable and stable PSC technologies.